Lack of Connection Between Midgut Cell Autophagy Gene Expression and BmCPV Infection in the Midgut of Bombyx mori. Issue 1 (10th July 2015) - Yang, Xiaobing; Wu, Suli; Wu, Yongpeng; Liu, Yang; Qian, Yonghua; Jiao, Feng
Abstract : Autophagy is associated with multiple biological processes and has protective and defensive functions with respect to immunity, inflammation, and resistance to microbial infection. In this experiment, we wished to investigate whether autophagy is a factor in the midgut cell response of Bombyx mori to infection by the B. mori cytoplasmic polyhedrosis virus (BmCPV). Our results indicated that the expression of three autophagy-related genes (BmAtg8, BmAtg5, and BmAtg7) in the midgut did not change greatly after BmCPV infection in B. mori . Basal ATG8/ATG8PE protein expression was detected in different B. mori tissues by using western blot analysis. Immunohistochemistry showed that the ATG8/ATG8PE proteins were located mainly in the cytoplasm. ATG8/ATG8PE protein levels decreased at 12 and 16 h after BmCPV infection. Our results indicate that autophagy responded slightly to BmCPV infection, but could not prevent the invasion and replication of the virus.